KAJIAN PEMBERIAN PAKAN BERBAHAN BAKU LOKAL DENGAN KANDUNGAN PROTEIN YANG BERBEDA TERHADAP PERTUMBUHAN IKAN GURAME (Osphronemus goramy Lac.) - Aditya Kusuma Nugroho; Siti Hudaidah; Limin Santoso (Jurnal Akuakultur Rawa Indonesia, 2021)
Gourami fish (Osphronemus goramy Lac.) is a freshwater fish commodity that has high economic value because its very popular with all people. But the feed commonly used by gourami fish cultivators is factory-made feed, which is a commercial feed that usually costs quite a lot of money due to the material for making commercial feed, some of which still import from abroad. Therefore it is necessary to find a solution to reduce the cost of cultivation production by replacing commercial feed with homemade feed made from local raw materials. The purpose of this study was to examine the use of local raw materials formulated to make feed suitable for the growth of gourami fish (Osphronemus goramy Lac.) And to analyze the production costs of goramy feed made from local raw materials. This study consisted of 4 treatments and 3 replications using the completely randomized design (CRD) method. The treatments consisted of treatment A (30% protein), treatment B (33% protein), treatment C (36% protein), and treatment D (commercial). The results of this study indicate that the treatment of feed A, B, and C produced the same growth as commercial feed, and treatment of feed A resulted in the lowest feed production costs compared to other treatments. Key word: feed, growth, local raw materials, Oshphronemus goramy